Minat Berwirausaha Mahasiswa Ditinjau Dari Self Efficacy Dan Adversity Quotient - Rita Ningsih; Arfatin Nurrahmah (Universitas Hamzanwadi, 2020)
The purpose of this research is to know the influence between self efficacy and adversity quotient on entrepreneurial interests of students, the effect of self efficacy on student entrepreneurial interests, and the effect of adversity quotient on student entrepreneurial interests. The method used is survey. Samples were obtained using simple random sampling technique as many as 105 students took entrepreneurship courses at one of the PTS in Jakarta. Data analysis is done using the help of the SPSS-16 program. Test requirements the analysis used is the test of normality, linearity test and multicolinearity test. The hypothesis test using a correlational test is followed by a double regression test. Based on the results of the research, the results that: 1) there are influence of self efficacy and adversity quotient jointly towards entrepreneurial interest. Self efficacy and adversity quotient contributions to entrepreneurial interest of 45.7% of the remaining 54.3% are donated by variables other than self efficacy and adversity quotient; 2) there is self efficacy influence on entrepreneurial interest, and 3) there is adversity quotient influence on entrepreneurial interest